Correlation between Sever Anemia and Pregnancy Complications - Ikram Ullah; Iqbal, Ayesha; Afridi, Sana; Zafar, Saman; Wahid, Nazia; Yousaf, Munazza (Indus Journal of Bioscience Research, 2025)
This prospective observational study aimed to assess the impact of anemia severity on maternal and perinatal outcomes in 200 pregnant women. The participants were categorized into three groups based on their hemoglobin levels: mild anemia (10.0–10.9 g/dL), moderate anemia (7.0–9.9 g/dL), and severe anemia (<7.0 g/dL). The majority of participants (60%) had moderate anemia, followed by 25% with mild anemia and 15% with severe anemia. The study found that as anemia severity increased, maternal and perinatal risks also escalated. Specifically, the incidence of preterm delivery was 8% in the mild anemia group, 20% in the moderate anemia group, and 40% in the severe anemia group. Similarly, postpartum hemorrhage (PPH) occurred in 2% of women with mild anemia, 10% with moderate anemia, and 20% with severe anemia. Cesarean section rates were 20% for mild anemia, 30% for moderate anemia, and 35% for severe anemia. Prolonged hospital stays (more than 7 days) were more common in severely anemic women (20%) compared to 7% in the moderate group and 4% in the mild anemia group. Maternal mortality was observed in one case (3%) in the severe anemia group. Perinatal outcomes showed a marked increase in low birth weight (LBW) with anemia severity. In the severe anemia group, 45% of newborns had a birth weight of less than 2.5 kg, compared to 33% in the moderate anemia group and 16% in the mild anemia group. NICU admissions were required for 30% of neonates in the severe anemia group, 15% in the moderate anemia group, and 8% in the mild anemia group. Perinatal mortality was 3.3% in the severe anemia group, compared to 1.7% in the moderate anemia group and 0% in the mild anemia group. The average birth weight was lowest in the severe anemia group (2.2 kg), followed by 2.4 kg in the moderate group and 2.7 kg in the mild group. Treatment interventions revealed that blood transfusions resulted in the highest increase in hemoglobin levels (3.0 g/dL), followed by intravenous iron (2.5 g/dL) and oral iron supplements (1.5 g/dL). In terms of mode of delivery, 76% of women with mild anemia had normal vaginal deliveries, compared to 60% in the moderate anemia group and 53% in the severe anemia group. Cesarean sections were more frequent in the severe anemia group (35%) than in the mild anemia group (20%). Postpartum hemorrhage rates increased with anemia severity, with 33% of severely anemic women requiring blood transfusions post-delivery, compared to 13% in the moderate anemia group and 4% in the mild anemia group. These findings highlight the significant maternal and neonatal health risks associated with severe anemia, emphasizing the need for early detection, appropriate treatment, and close monitoring to improve pregnancy outcomes.